Guiren Runchang granules alleviate slow transit constipation in mice by modulating gut microbiota and short-chain fatty acids - Bai, Xinfeng; Wang, Yachao; Wang, Kai; Chu, Weihua; Bai, Tianyu (Frontiers in Microbiology, 2025)
Guiren Runchang Granules (GRG), a traditional Chinese medicine (TCM) formulation, has demonstrated effectiveness in treating slow transit constipation (STC). This study investigated the therapeutic effects of GRG on constipated mice, focusing on its role in restoring intestinal micro-ecology. The results showed that GRG treatment significantly improved defecation in STC mice and ameliorated intestinal histopathological damage. GRG effectively normalized colonic and serum motility-related hormone levels (5-HT, SP, MTL, and SS) with comparable efficacy to mosapride, a prokinetic agent. In addition, GRG treatment restored the balance of the gut microbiota and increased the levels of short-chain fatty acids (SCFAs). Specifically, the relative abundance of the genera Alloprevotella and Muribaculum increased, while that of Prevotellaceae_NK3B31_group, Ruminococcus, and Lachnospiraceae_UCG-001 decreased. These microbiota changes were significantly correlated with SCFAs level, motility-related hormone concentrations, and defecation phenotype. Our findings highlight GRG’s multi-target mode of action involving microbiota modulation, SCFAs restoration, and hormonal regulation, positioning it as a promising alternative to conventional therapies for STC.